Kontribusi Badan Usaha Milik Desa (BUMDes) Syariah dalam Meningkatkan Pendapatan Asli Desa (PADes) Desa Bangun Seranten Kecamatan Muara Tabir Kabupaten Tebo - Irfana, Azza (Jurnal Ilmiah Universitas Batanghari Jambi, 2024)
The aim of this research is to determine the process of managing BUMDes Berkah Abadi's funds in PADes, the contribution of BUMDes Berkah Abadi in improving PADes, and the obstacles and solutions for BUMDes Syariah Berkah Abadi in its contribution to PADes. The method used in this research is qualitative. The results of this research show that the contribution of BUMDes to PADes is the activity process in an effort to design interactions between BUMDes and the Village Government so that they can distribute PADes well and create the ability of BUMDes with their business units that sell palm oil fertilizer to increase PADes, namely, by designing BUMDes in interaction. village government every month or every three months, BUMDes provides reports on BUMDes activities.